Prototype sistem pakar diagnosis penyakit diabetes - Catur Edi Widodo (Youngster Physics Journal, 2017)
Every member of the community can experience a variety of diseases. The disease can be known from the symptoms it produces, but to know the exact type of disease, needed a doctor or a health professional. Since the number of doctors or health professionals is very limited and can not overcome the problems of the community at the same time, a system that has the capability of a doctor or health professional is required, which in this system contains the expertise of a physician or health professional on diseases and diseases. In this study was designed expert system using rule base (reason based reasoning) with forward chaining and backward chaining inference method that is intended to assist the community in diagnosing the disease. This disease diagnostic expert system developed has advantages in ease of access and ease of use. With the features that are owned, expert systems for the diagnosis of diseases that built can be used as a tool for disease diagnosis and can be accessed by the public to overcome the problem of limited number of doctors or health experts in helping people diagnose the disease.Keywords: disease, expert system, backward chaining, forward chaining, rule-based reasoning